PUBLIC MEDIATION POLICY AS AN INSTRUMENT FOR THE SEARCH OF PARENTAL CONSENSUS AND ITS REFLECTIONS ON THE EFFECTIVENESS OF THE SHARED GUARD - Edwirges Elaine Rodrigues; Maria Amália de Figueiredo Pereira Alvarenga (Revista Eletrônica do Curso de Direito da UFSM, 2018)
As a result of the reform of the Judiciary, the National Council of Justice, the new social policy, in order to organize and solidify at the national level, not only services rendered in judicial processes, but also other conflict resolution mechanisms, in non-adversaries, such as mediation. Family mediation shows the right way to resolve child custody conflicts. It is known that in order to be successful in the application of shared custody, there must be a minimum of dialogue between parents, since all decisions about children must be taken together. On the other hand, disagreement and rancor are common at the end of relationships. Thus, mediation becomes an important instrument for the realization of joint custody, in order to provide parents with the necessary understanding to distinguish conjugality from parenthood, since it comes to an end, but it remains, and the principles of responsible parenting and the best interests of the children. Thus, the method chosen for this research was the deductive, in which a review of the bibliography related to Family Law and, in particular, to the institute was shared custody, as well as the importance of family mediation, both in the Law of Mediation as well as in the New Code of Civil Procedure, as an instrument for the implementation of this type of custody.